2015
DOI: 10.3892/mmr.2015.3615
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaric acid B exerts antitumor activity via suppression of the Akt signaling pathway in HeLa cervical cancer cells

Abstract: Pseudolaric acid B (PAB) is a diterpene acid isolated from the bark of the root and trunk of Pseudolarix kaempferi Gordon (Pinaceae), which has demonstrated cytotoxic effects against various types of cancer. However, the mechanisms underlying the anticancer effects of PAB have remained to be elucidated. In the present study, the effects of PAB on the viability and apoptosis of HeLa cells were investigated by MTT assay, flow cytometric analysis of Annexin V-fluorescein isothiocyanate/propidium iodide staining, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, most of findings on PAB-induced apoptosis focused on intrinsic apoptotic pathway. For examples, PAB inhibits mitochondria-mediated apoptosis pathways in human gastric carcinoma BGC-823 and MKN-45 cells and cervical cancer HeLa cells through the modification of the ratio of Bax/Bcl-2 [12,37]. PAB also induced apoptosis via proteasome-mediated protein degradation of Bcl-2 in human prostate cancer DU145 cells [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of findings on PAB-induced apoptosis focused on intrinsic apoptotic pathway. For examples, PAB inhibits mitochondria-mediated apoptosis pathways in human gastric carcinoma BGC-823 and MKN-45 cells and cervical cancer HeLa cells through the modification of the ratio of Bax/Bcl-2 [12,37]. PAB also induced apoptosis via proteasome-mediated protein degradation of Bcl-2 in human prostate cancer DU145 cells [38].…”
Section: Discussionmentioning
confidence: 99%
“…[7]. Among the studies, it has shown that PAB has strong cytotoxic effects on various types of cancers, including colorectal cancer, gastric cancer, liver cancer, prostate cancer, lung cancer, melanoma, and leukemia [8,9,10,11,12,13,14,15,16]. However, there has not been yet a single research on HNCs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the diterpenoid C from Radix curcumae in human colon adenocarcinoma SW620 cells significantly inhibited cell proliferation and induced apoptosis by MAPK signalling and caspase‐3 dependent pathways (Shen et al , ). The other antiproliferative and apoptosis‐inducing diterpenes are pseudolaric acid B (Yu et al , ), oridonin (Yang et al , ), pseudolaric acid B (Li and Hong, ), crypotanshinone (Yao et al , ), tanshinone IIA (Zhang et al , ) and tonantzitlolone A and its synthetic enantiomer (Pfeffer et al , ). Penitrem A in MDA‐MB‐231 mammary cancer cells exerted antiproliferative, antimigratory and total β‐catenin suppressing effects (Sallam et al , ).…”
Section: Diterpenic Anticancer Traitsmentioning
confidence: 99%
“…The other antiproliferative 700 M.T. ISLAM and apoptosis-inducing diterpenes are pseudolaric acid B (Yu et al, 2015), oridonin (Yang et al, 2015a), pseudolaric acid B (Li and Hong, 2015), crypotanshinone (Yao et al, 2015b), tanshinone IIA (Zhang et al, 2016b) and tonantzitlolone A and its synthetic enantiomer (Pfeffer et al, 2016). Penitrem A in MDA-MB-231 mammary cancer cells exerted antiproliferative, antimigratory and total β-catenin suppressing effects (Sallam et al, 2013).…”
Section: Effects On Cell Proliferation and Differentiationmentioning
confidence: 99%
“…7 Moreover, the promising activities of pseudolaric acid B have been reviewed. 8 Anti-cancer activities can be expected since pseudolaric acids are highly cytotoxic on cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%